STRATEGI PEMASARAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI ERA PANDEMI COVID-19 (Studi Pada UMKM Gerbang Ranomeeto – Kendari) (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
To find out which marketing strategy is best applied to MSME actors at the Ranomeeto gate in the midst of the covid-19 pandemic, To find out the obstacles faced by MSME actors at the Ranomeeto gate in implementing marketing strategies in order to survive in the midst of the covid-19 pandemic, To find out solutions for MSMEs at the Ranomeeto gate in the face of the covid-19 pandemic in order to maintain their business. The research design used is descriptive research. The results showed that the MSME Strategy at the Ranomeeto gate in the midst of the Covid-19 Pandemic had shown a good strategy, including in the dimensions of Marketing, Production, Personal Sales, Advertising, Sales Promotion, Publication and Public Relations. The implementation of marketing strategies plays a very important role in increasing sales for small and medium enterprises (MSMEs) at Ranomeeto Gate. In implementing the marketing strategy of small and medium enterprises (MSMEs) at Ranomeeto Gate, currently four components of marketing strategy theory have been applied, namely segmentation, targeting, positioning, and differentiation. However, the implementation of the marketing strategy of small and medium enterprises (MSMEs) at Ranomeeto Gate is currently not optimal. During the Covid-19 pandemic, there was a decline in the sales performance of MSMEs business actors. The decline occurred in the early phase of the Covid 19 pandemic in Kendari City. This also resulted in a decrease in the use of labor so that some workers had to be laid off.